(untitled) (Research, Society and Development, 2020)
This study aimed to analyze physiotherapeutic care in patients with HIV/AIDS at a referral hospital in the state of Paraíba from July 2017 to July 2018. The sample involved 79 records and 17 physical therapists, a study retrospective and prospective transversal, exploratory / descriptive with quantitative and qualitative approach. The inclusion criteria for inclusion of records were to have physical therapy records, to be between 18 and 90 years old and not to be distressed. In relation to physiotherapists using the inclusion and exclusion criteria, which were related to age over 21 years and under 60 years, not on vacation or leave and work in the outpatient, nursing or ICU, resulted in 17 professionals in the collection. It was observed that patients had a median of three daily sessions of physiotherapy with a standard deviation of + 0.9 which varied from one to three times a day during their stay in the hospital. Categorizing in motor physiotherapy, 68 patients received such assistance with an average of 13.1 days of care. Regarding respiratory physiotherapy, 58 patients performed techniques with the professional, having an average of 12.9 days during their hospitalization. This study had a deepening of the knowledge about subject that aimed to contribute in the clinical practice of the professional of physiotherapy. Further research is needed with larger samples aiming to show with greater precision and significance the results and importance of physiotherapy to patients with HIV/AIDS.